2010
DOI: 10.2174/1874331501004010023
|View full text |Cite
|
Sign up to set email alerts
|

Granular Size Effect of Clinoptilolite on Maize Seedlings Growth

Abstract: Clinoptilolite has been successfully used in growing media for containerized horticultural and floricultural production. However, limited data exist on the effects and interaction between particle size and organic nutrient enrichment of the clinoptilolite. One granular (1-3 mm) and micronized (<30 μm) clinoptilolite was added to quartz sand, an inert growing substrate, at two doses (0.1% and 3% v/v), without or with addition of wine vinasse as nutrient source at four concentrations (0 mg F L subst -1 , 10 mg F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…However, in another study, the highest increase of weight or length ratio of maize primary root was obtained for treatment with micronized clinoptilolite at the lower dose of 0.1% compared to higher dose of 3.0% (Trinchera et al, 2010).…”
Section: Plant Height At 65 Dapmentioning
confidence: 86%
“…However, in another study, the highest increase of weight or length ratio of maize primary root was obtained for treatment with micronized clinoptilolite at the lower dose of 0.1% compared to higher dose of 3.0% (Trinchera et al, 2010).…”
Section: Plant Height At 65 Dapmentioning
confidence: 86%
“…On the other hand, rhizospheric effect may be influenced by zeolite application, too. Trinchera et al (2010) Table 3. The fertilizer treatments influence on dehydrogenase activity (TPF μg/g/h × 10 -5 ); more effective in its interaction with root surface.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Their incorporation in soil was found to increase crop yield and promote nutrient use efficiency (Ramesh & Reddy, 2011). The most abundant zeolite in nature is clinoptilolite (Bernardi et al, 2016) often used as a source of potassium and ammonium ions (Trinchera et al, 2010). Simić et al (2013) suggested that plants may show good response on clinoptilolite used as a fertilizer carrier, and that it has a potential to improve cattle farm -manureorganic fertilizer system for forage crops.…”
mentioning
confidence: 99%
“…Groleau-Renaud et al (1998) membuktikan bahwa pertumbuhan akar tanaman jagung sangat dipengaruhi oleh hambatan mekanik dari media tumbuh. Umumnya diketahui bahwa pengaruh hambatan mekanik terhadap morfologi akar ditentukan oleh sangat berkurangnya laju pemanjangan akar dan bertambahnya diameter dari akar-akar yang terhambat (Trinchera et al, 2010). Boeuf-Tremblay et al (1995) selanjutnya menunjukkan bahwa bibit jagung dan pertumbuhan tanaman sangat dipengaruhi oleh hambatan mekanik melalui simulasi dengan menambahkan butiran-butiran gelas (glass beads) ke dalam media tumbuh yang steril, yang menghasilkan akar-akar yang lebih pendek dan lebih berat per satuan panjang.…”
Section: Pengaruh Zeolit-urine Terhadap Pertumbuhan Tanaman Jagung Seunclassified